(untitled) (Bangladesh Journal of Zoology, 2025)
Street foods offer affordable, nutritious, and accessible food options for many urban residents in developing countries. Most university students in Bangladesh rely on street foods due to their appealing appearance. However, these foods are often prepared and served under poor hygienic conditions, making them potential sources of parasitic contamination and faeco-oral disease transmission. Considering the increasing demand for these food items among students, a study was carried out on 50 food samples comprising three types of foods: tamarind water of snacks (27 samples), fruit juices (16 samples), and sliced fruits (7 samples), and 50 corresponding fecal samples from vendors of Dhaka University Campus to assess the parasitic contamination in street foods. Food vendors were also asked to fill a questionnaire on their socio-economic and demographic profile and hygienic practices. It was found that 46 (92%) food samples were contaminated with 6 different types of parasites (Blastocystis hominis, Cystoisospora belli, Hymenolepis diminuta, Hymenolepis nana, Ascaris lumbricoides, and Trichuris trichiura); their prevalence ranged between 4% and 48%. Besides, 92% of vendors were infected with 7 different parasites; the highest prevalence was observed for B. hominis (66%). Out of 4 identified parasites in food and corresponding stool samples, B. hominis (40%) was the most prevalent parasite, followed by C. belli (32%), A. lumbricoides (26%), and H. nana (2%). Fisher’s exact tests revealed that there was a significant association between the presence of B. hominis (p=0.002) and C. belli (p=0.001) in stool and its presence in food. We also found a significant association (at 5% significant level) between the presence of C. belli in food and the water sterilization practice of the food vendors (p-value=0.03). The study shows the serious health risks resulting from poor hygiene practices. So, we need to take immediate action to mitigate the significant public health risks, particularly those who consume street food in the area. Bangladesh J. Zool. 53(2): 201-208, 2025